Genetic Variation in Hanönü (Kastamonu)-Günlüburun Anatolian Black Pine (Pinus nigra Arnold. subsp.caramanica (Lamb.) Holmboe) Clonal Seed Orchard According to Some Needles Characters* - Sevik, Hakan; Ayan, Sezgin; Yiğit, Nurcan (International Symposium on Biology of Rare and Endemic Plant Species, 26-29 May, Fethiye-Mugla/Turk, 2010)
Anatolian Black Pine (Pinus nigra Arnold. subsp. pallasiana (Lamb.) Holmboe) is one of the most common and important forest tree species in Turkey. Meanwhile, the stands of this species occupy roughly 4,2 million ha, of which about 1,8 million ha are considered to be non productive forest. Also, this pine species is most important species which can be spread to the steppe regions in Anatolia. The semi-arid steppe regions evaluate as potential afforestation areas. Actually, the seed demand for this species is mainly supplied from current 53 of seed orchards and 79 of seed stands. Most of these seed orchards are still rather young and mainly established after 1990’s. The main objective of Anatolian black pine seed orchards is the production of genetically improved seed for reforestation purpose. The objective of this study was to investigate the genetic variation in Hanönü-Günlüburun Anatolian Black Pine (Pinus nigra Arnold. subsp. pallasiana (Lamb.) Holmboe) clonal seed orchard using eight morphological and anatomical needles characters. For this purpose; 3 sample trees from 30 clones and 10 needles from each samples tree were selected. Totally 900 sample needle were used for this study. Nine morphological and anatomical traits (needle length, needle width, needle thickness, sheath thickness, number of rows of stomata in the dorsal and ventral faces, number of stomata per cm of needle length in the dorsal and ventral faces) were determinate in 900 needle. The results showed that; there were significant differences between clones according to eight morphological and anatomical needles characters.
Keywords: Anatolian Black Pine; Seed Orchard; Genetic Variation; Needles Characters